2017
DOI: 10.1089/cap.2015.0067
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity and Regulation Following Citalopram Therapy in Children and Adolescents with Anxiety Disorders

Abstract: Citalopram therapy improves reappraisal ability in children and adolescents with anxiety. However, the improvement in other examined emotional reactivity indices occurred in both medicated and waitlisted groups. It is possible that these findings may have implications for understanding the pathophysiology of anxiety in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…In accordance with studies conducted across numerous animal taxa, the administration of the selective serotonin reuptake inhibitor citalopram monotonically decreased the observed anxiety-related response [9,41,42]. The possibility of modulating anxiety-related behavior through serotonergic agonists is widely documented in zebrafish [57][58][59][60].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In accordance with studies conducted across numerous animal taxa, the administration of the selective serotonin reuptake inhibitor citalopram monotonically decreased the observed anxiety-related response [9,41,42]. The possibility of modulating anxiety-related behavior through serotonergic agonists is widely documented in zebrafish [57][58][59][60].…”
Section: Discussionsupporting
confidence: 62%
“…Ethanol and citalopram have been selected based on their known efficacy in modulating fear-and anxiety-related behaviors across a number of taxa ranging from humans [40,41] to rodents [42,43] and fish [9,23,44]. In zebrafish, we have already demonstrated that ethanol administration modulates individual behavior in response to the same predatorial stimulus adopted in this study [26].…”
Section: Introductionmentioning
confidence: 99%
“…ED leads to psychopathology and a number of externalizing and internalizing symptoms, including anxiety, mood dysregulation, impulsiveness, behavioral issues, and serious debilitating social problems. Two forms of stress related sequelae have to be considered: (i) acute emotional cues triggering experiential, behavioral, central and peripheral physiological systems ( 458 ), and (ii) chronic mental stress resulting from continuous burdens, such as maltreatment or familial discord, leading to personality modification, ED, and related problems.…”
Section: Resultsmentioning
confidence: 99%
“…Antidepressants and mood stabilizing medication - alleviating anxiety, improving mood, and decreasing maniac symptoms ( 458 , 461 )…”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported a range of effects with SSRI treatment either alone or in combination with CBT which are associated with clinical response, although most studies use self-report measures making it difficult to understand the underlying mechanisms of change. These include improved emotional reappraisal, 92 enhanced problem solving ability, 93 decreased perfectionism, 94 decreased hopelessness, 95 improved coping efficacy, 96 decreased negative interpretative bias, 97 reduced somatic symptoms, 98 reduced social distress and behavioural avoidance 99 and improved sleep. 100,101…”
Section: Corticolimbic Circuitry and Affective Processingmentioning
confidence: 99%